Study of The Utilization of Pineapple Leaves (Ananas cosmosus) as Adsorbent for Lowering Copper Ion Content (Cu2+), Iron (Fe3+), and Zinc (Zn2+) in the Water. - Chairuddin (Talenta Publisher, 2020)
. It has been conducted the use of pineapple leaf (Pineapple cosmosus) as an adsorbent to reduce ion copper (Cu2+), iron (Fe3+), and zinc (Zn2+) contents in water. First pineapple leaf powder is cut to pieces, dried, finely ground, and activated with 10% HCl by soaking for 24 hours. Two grams of pineapple leaf powder, which was previously activated by 10% HCl added into each 100 mL ions of copper (Cu2+), iron (Fe3+), and zinc (Zn2+) standard solution 20 mg/L, stirred homogeneously, and left for 24 hours, then filtered. The concentration ions of copper (Cu2+), iron (Fe3+), and zinc (Zn2+) infiltrate were determined by using Atomic Absorption Spectrophotometer (AAS). The result of this research showed that pineapple leaf powder-activated 10% HCl can absorb 95.98% of copper (Cu2+), 79.16% of iron (Fe3+), and 88.71% of zinc (Zn2+).